A Single‐Atom Cobalt Catalyst for the Fluorination of Acyl Chlorides at Parts‐per‐Million Catalyst Loading. (2nd September 2022) - Li, Wen‐Hao; Ye, Bo‐Chao; Yang, Jiarui; Wang, Ye; Yang, Chang‐Jie; Pan, Ying‐Ming; Tang, Hai‐Tao; Wang, Dingsheng; Li, Yadong
Abstract: Improving the stability of sensitive catalytic systems is an emerging research topic in the catalysis field. However, the current design of heterogeneous catalysts mainly improves their catalytic performance. This paper presents a single‐atom catalyst (SAC) strategy to improve the cobalt‐catalysed fluorination of acyl chlorides. A stable Co−F intermediate can be formed through the oxidative fluorination of Co1 −N4 @NC SAC, which can replace the unstable high‐valent cobalt catalytic system and avoid the use of phosphine ligands. In the SAC system, KF can be employed as a fluorinating reagent to replace the AgF, which can be applied to various substrates and scale‐up conversion with high turnover numbers (TON=1.58×10 6 ). This work also shows that inorganic SACs have tremendous potential for organofluorine chemistry, and it provides a good reference for follow‐up studies on the structure‐activity relationship between catalyst design and chemical reaction mechanisms. Abstract : A Co single‐atom catalyst was synthesized via thermal decomposition of a zeolitic imidazolate framework (ZIF). The Co1 −N4 @NC catalyst generated a stable Co−F intermediate in situ through an oxidative fluorination pathway to replace the substitution fluorination of the unstable high‐valent Co system. In the presence of Co−F intermediates, KF can be used to replace AgF. Co1 −N4 @NC exhibited ultrahigh catalytic activity for the fluorination of acyl chlorides.